Morbius [videorecording (DVD)] - Leto, Jared, 1971-; Smith, Matt, 1982-; Arjona, Adria, 1992-; Harris, Jared, 1961-; Madrigal, Al, 1971-; Tyrese; Keaton, Michael, 1951- (Sony Pictures Home Entertainment, 2022)
One of the most compelling and conflicted characters--the enigmatic antihero Michael Morbius--comes to the big screen! Dangerously ill with a rare blood disorder and determined to save others suffering his same fate, Dr. Morbius attempts a desperate gamble. While at first it seems to be a radical success, a darkness inside him is unleashed. Will good override evil -- or will Morbius succumb to his mysterious new urges?